Morphology of porang (Amorphophallus muelleri) in the Citarum Watershed, West Java, Indonesia - ASEP ZAINAL MUTAQIN; MARZHAVIRA AZLIKA KHRISNAN; JOKO KUSMORO; JOHAN ISKANDAR; RULY BUDIONO; MADIHAH MADIHAH; MOHAMAD NURZAMAN; TIA SETIAWATI; RUSDI RUSDI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Mutaqin AZ, Khrisnan MA, Kusmoro J, Iskandar J, Budiono R, Madihah, Nurzaman M, Setiawati T, Rusdi. 2024. Morphology of porang (Amorphophallus muelleri) in the Citarum Watershed, West Java, Indonesia. Biodiversitas 25: 2656-2662. The porang plant (Amorphophallus muelleri Blume) is a plant from the Araceae family that grows widely in various regions in Indonesia, including West Java Province. The porang plant contains various compounds, especially glucomannan, which can be used as food, cosmetics, medicines, etc., making it a prospective agricultural commodity widely cultivated by farmers. Like other plants, the characteristics of the porang plant are dependent on the environmental growing conditions. This research aims to determine the morphological characteristics of porang plants in several locations under various growing environments in the Citarum watershed, West Java Province. This research makes use of qualitative and quantitative approaches. The sampling technique was exploratory, with observation and interviews as additional data sources. Exploration was carried out to find the growing porang locations. Observations were carried out to observe or record the morphological characteristics and growing environment of porang. Interviews were conducted with competent community groups regarding the porang plant, such as farmers, to enrich information, especially regarding morphology and the growing environment. The research shows that porang are found in several locations, including the Citarum watershed. Unfortunately, this research observed intensively porang grown in Soreang Sub-district, Bandung District, Cipatat Sub-district, West Bandung District, and East Cikalong Sub-district, West Bandung District. Furthermore, specific observations of porang showed morphological differences in different growing environments in several locations, such as differences in light intensity, temperature, and soil pH.